2009
DOI: 10.1152/ajpheart.00367.2009
|View full text |Cite
|
Sign up to set email alerts
|

sGCα1β1attenuates cardiac dysfunction and mortality in murine inflammatory shock models

Abstract: Buys ES, Cauwels A, Raher MJ, Passeri JJ, Hobai I, Cawley SM, Rauwerdink KM, Thibault H, Sips PY, Thoonen R, ScherrerCrosbie M, Ichinose F, Brouckaert P, Bloch KD. sGC␣ 1␤1 attenuates cardiac dysfunction and mortality in murine inflammatory shock models. Am J Physiol Heart Circ Physiol 297: H654 -H663, 2009. First published June 5, 2009 doi:10.1152/ajpheart.00367.2009.-Altered cGMP signaling has been implicated in myocardial depression, morbidity, and mortality associated with sepsis. Previous studies, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 59 publications
3
37
2
Order By: Relevance
“…Only male mice were studied. Generation of sGCα1 -/-S6 (generated on the S6 background) and sGCα1 -/-B6 mice (backcrossed 8 generations with B6 mice from The Jackson Laboratory) was described previously (18,21). WT B6 and WT S6 mice were purchased from The Jackson Laboratory and Taconic, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only male mice were studied. Generation of sGCα1 -/-S6 (generated on the S6 background) and sGCα1 -/-B6 mice (backcrossed 8 generations with B6 mice from The Jackson Laboratory) was described previously (18,21). WT B6 and WT S6 mice were purchased from The Jackson Laboratory and Taconic, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The F1 offspring were subsequently intercrossed (16 breeding pairs) to yield F2 offspring. MAP was measured invasively in 284 male F2 offspring at 4 months of age, as previously described (18,21). Briefly, mice were anesthetized by i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7B). As PTH is known to have hypotensive effects on the vasculature (18), and previous studies in rats show that PTH-induced reductions in systemic blood pressure can result in reduced glomerular blood flow (19), we assessed the effects of PTH administration on systemic blood pressure in WT and PD mice (20). Following a brief i.v.…”
Section: Effects Of Pth Analogs On Signaling In Bone and Kidney Of Wtmentioning
confidence: 99%
“…We treated our patient with nitrates until the heart recovery, aiming to improve myocardial perfusion. Buys et al reported in mice a protective effect of nitric oxide against cardiac dysfunction caused by inflammatory shock, known to interfere with mitochondrial respiration, mediated by soluble guanylate cyclase producing cyclic guanosin monophosphate 7 . Cauwels et al found that nitrite had a protective effect on mitochondrial respiration and improved cellular energetics against TNFmediated inhibition of complexes I and IV of the mitochondrial respiratory chain 8 .…”
mentioning
confidence: 99%